A fluorine-free oil-proof agent for pulp food containers and dining utensils and its production process
By developing a fluorine-free oil-proofing agent, using specific ratios and process steps to form a dense film structure, the problem of harmful substances in existing waterproof and oil-proof food packaging paper is solved, and efficient and environmentally friendly water-proof and oil-proofing are achieved. Effect.
Patent Information
- Application Number
- CN202310353525.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-04
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-04-04
AI Technical Summary
Existing waterproof and oil-resistant food packaging papers contain harmful perfluorooctanate/perfluorooctan sulfonate and long-chain perfluoroalkyl compounds, and the materials are difficult to degrade, causing environmental pollution.
Develop a fluorine-free oil-proofing agent, including-2-ethylhexyl acrylate, binders, modified starch, emulsified paraffin, fillers and deionized water, to form a denser through specific ratios and process steps. membrane structure to improve oil resistance.
It realizes the effective application of fluorine-free oil-proofing agent in pulp food containers and catering utensils. It can maintain the constant temperature of 95℃ hot water and 95℃ cooking oil for 36 hours, significantly improving the waterproof and oil-proofing effect, and is safe and environmentally friendly. No harmful substances.
Smart Images

Figure GHA0000007156880000121 
Figure GHA0000007156880000131 
Figure GHA0000007156880000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil-proofing agents, in particular to a fluorine-free oil-proofing agent for pulp food containers and dining utensils and a production process thereof. Background Art
[0002] As people's demands for a better life become higher and higher, the use of food packaging paper is also increasing. Commonly used food packaging papers in life, such as takeaway boxes and fast food packaging, need to have good waterproof and oil-proof properties.
[0003] At present, most of the waterproof and oil-proof food packaging papers on the market are coated papers. Coated papers use an extrusion composite process to coat plastic particles such as polyethylene (PE) and polypropylene (PP) on the surface of paper through a casting machine. Coated papers have excellent performance in terms of water and oil resistance, but such materials are difficult to degrade or degrade very slowly in nature, causing great pollution to the human environment. In addition, fluorine-containing polymers can form a thin film on the paper fibers. The long fluorine-containing side chains in the film layer can stretch and align in a directional manner on the interface. The film layer can significantly reduce the surface energy of the substrate, which is lower than that of general liquids, so it has waterproof and oil-proof properties. However, these long-chain fluoroalkyl compounds will produce perfluorooctanoic acid ammonium / perfluorooctane sulfonate (PFOA / S) that is harmful to the environment and human body during use, and the waterproof and oil-proof properties of short-chain perfluoroalkyl compounds decrease as the number of carbon atoms decreases.
[0004] Therefore, it is necessary to develop non-toxic, environmentally friendly fluorine-free oil-proof agents to solve the current problems and shortcomings in oil-proofing in the field of pulp molding products. Summary of the invention
[0005] In order to solve the above-mentioned deficiencies of the prior art, the object of the present invention is to provide a production process of a fluorine-free oil-proofing agent for pulp food containers and tableware to overcome the defects in the prior art.
[0006] In order to achieve the above-mentioned purpose of the present invention, the present invention also provides a fluorine-free oil-proof agent for pulp food containers and tableware, comprising the following raw materials in parts by weight: 2-4 parts of 2-ethylhexyl acrylate, 3-5 parts of adhesive, 2-4 parts of modified starch, 5-10 parts of emulsified paraffin, 25-35 parts of filler, and 45-55 parts of deionized water, wherein the adhesive is selected from one or more of hydroxypropyl methylcellulose, low-substituted hydroxypropyl cellulose, polyvinyl pyrrolidone, polyacrylamide, and chitosan, and the filler is selected from one or more of calcium carbonate, quartz powder, titanium dioxide, montmorillonite, and silicon dioxide.
[0007] As a further description of the fluorine-free oil-proofing agent for pulp food containers and tableware of the present invention, preferably, it includes the following raw materials in parts by weight: 3 parts of 2-ethylhexyl acrylate, 4 parts of adhesive, 3 parts of modified starch, 8 parts of emulsified paraffin, 30 parts of filler, and 50 parts of deionized water.
[0008] As a further description of the fluorine-free oil-proofing agent for pulp food containers and tableware of the present invention, preferably, the modified starch is cationic starch or anionic starch.
[0009] As a further description of the fluorine-free oil-proofing agent for pulp food containers and dining utensils of the present invention, preferably, the particle size of the filler is 0.01-10 μm. Inorganic fillers in this particle size range are more easily dispersed in modified starch solutions.
[0010] In order to achieve another object of the present invention, the present invention also provides a production process of a fluorine-free oil-proofing agent for pulp food containers and tableware, the production process comprising the following steps:
[0011] (1) adding a binder and 2-ethylhexyl acrylate into deionized water, stirring and mixing at a low speed to obtain a mixed solution A; the binder is selected from one or more of hydroxypropyl methylcellulose, low-substituted hydroxypropyl cellulose, polyvinyl pyrrolidone, polyacrylamide, and chitosan;
[0012] (2) adding the modified starch into deionized water, stirring at a low speed at a temperature of 70-80° C. to obtain a modified starch solution;
[0013] (3) adding emulsified paraffin and a filler to the modified starch solution obtained in step (2), subjecting the mixture to ultrasonic vibration, and uniformly dispersing the mixture to obtain a mixed solution B; the filler is selected from one or more of calcium carbonate, quartz powder, titanium dioxide, montmorillonite, and silicon dioxide;
[0014] (4) When using, first mix the mixed solution A and the pulp evenly, then add the mixed solution B and continue to mix evenly, so that the mixed solution A and the mixed solution B can be used as the fluorine-free oil-proofing agent for pulp food containers and tableware. Preferably, the addition ratio of the fluorine-free oil-proofing agent is 6.25% of the pulp.
[0015] As a further description of the production process of the present invention, preferably, the fluorine-free oil-proofing agent comprises the following raw materials in parts by weight: 2-4 parts of 2-ethylhexyl acrylate, 3-5 parts of adhesive, 2-4 parts of modified starch, 5-10 parts of emulsified paraffin, 25-35 parts of filler, 45 parts of deionized water, 100 parts of fluorine-free oil-proofing agent, 2 ... 8 55 copies.
[0016] As a further illustration of the production process described in the present invention, preferably, the fluorine-free oil repellent comprises the following raw materials in parts by weight: 3 parts of 2-ethylhexyl acrylate, 4 parts of adhesive, 3 parts of modified starch, 8 parts of emulsified paraffin, 30 parts of filler, and 50 parts of deionized water.
[0017] As a further illustration of the production process of the present invention, preferably, the modified starch is cationic starch or anionic starch.
[0018] As a further illustration of the production process of the present invention, preferably, the particle size of the filler is 0.01-10 μm. Inorganic fillers in this particle size range are easier to disperse in the modified starch solution.
[0019] As a further illustration of the production process of the present invention, preferably, the stirring time in step (1) and step (2) is 20 to 30 minutes, and the stirring speed is 60 to 70 rpm.
[0020] As a further illustration of the production process of the present invention, preferably, in step (3), the product is placed in an ultrasonic cleaner with an ultrasonic frequency of 40 KHz for ultrasonic oscillation for 5 to 10 minutes.
[0021] As a further illustration of the production process of the present invention, preferably, in step (4), the solution A and the pulp are mechanically stirred for 5 to 25 minutes, and the solution B is added and mechanically stirred for another 5 to 25 minutes. When used, the stirring time of adding solution A and the stirring time of adding solution B can be shortened by 5 minutes.
[0022] The beneficial effects of the present invention are as follows:
[0023] 1) In the present invention, 2-ethylhexyl acrylate provides a low surface energy environment, and the filler is selected from one or more of calcium carbonate, quartz powder, titanium dioxide, montmorillonite, and silicon dioxide to fill the gaps between the fibers. Emulsified paraffin can cover and seal the hydrophilic groups on the fiber surface. The modified starch forms a denser film under the synergistic effect of the adhesive. The adhesive is selected from one or more of hydroxypropyl methylcellulose, low-substituted hydroxypropyl cellulose, polyvinyl pyrrolidone, polyacrylamide, and chitosan, which effectively improves the oil-proof effect of tableware. The pulp food container and dining utensils added with the fluorine-free oil-proofing agent prepared by the present invention are not penetrated after being kept at a constant temperature for 36 hours when containing 95°C hot water and 95°C edible oil.
[0024] 2) The fluorine-free oil-proofing agent prepared by the present invention is added into the slurry, which is safe and environmentally friendly and will not produce toxic and harmful substances to the human body. It is a healthy and environmentally friendly water-proofing and oil-proofing agent. DETAILED DESCRIPTION
[0025] In order to further understand the present invention, the following is a detailed description in conjunction with the attached preferred embodiments. This embodiment is only used to illustrate the technical solution of the present invention and is not intended to limit the present invention.
[0026] Materials preparation:
[0027] Polyacrylamide was purchased from Shandong Wankang Biotechnology Co., Ltd.
[0028] Hydroxypropyl methylcellulose was purchased from Henan Zongteng Food Additive Co., Ltd.
[0029] Low-substituted hydroxypropyl cellulose was purchased from Shandong Fengtai Biotechnology Co., Ltd.
[0030] Polyvinyl pyrrolidone was purchased from Wuhan Hongyi Biotechnology Co., Ltd.
[0031] 2-Ethylhexyl acrylate was purchased from Hubei Jusheng Technology Co., Ltd.
[0032] Modified starch was purchased from Zhengzhou Wanruida Chemical Products Co., Ltd. (CAS No.: 9063-38-1).
[0033] Emulsified paraffin was purchased from Foshan Hongsheng Chemical Co., Ltd.
[0034] Calcium carbonate was purchased from Anhui Weimao Biotechnology Co., Ltd.
[0035] Quartz powder was purchased from Guangdong Yuanlei Powder Co., Ltd.
[0036] Chitosan and titanium dioxide were purchased from Shandong Jiajiali Biotechnology Co., Ltd.
[0037] Montmorillonite was purchased from Guangzhou Zhanfei Chemical Technology Co., Ltd.
[0038] Silica was purchased from Wuxi Shengshi Hongcheng Biotechnology Co., Ltd.
[0039] Embodiment 1:
[0040] 3 parts by weight of polyacrylamide and 2 parts by weight of 2-ethylhexyl acrylate were added into 20 parts by weight of deionized water, and the mixture was stirred at a low speed of 60 rpm for 20 minutes to obtain a mixed solution A after being uniformly mixed.
[0041] 2 parts by weight of modified starch were added to 25 parts by weight of deionized water, and the mixture was stirred evenly at a low speed of 60 rpm at a temperature of 70° C. for 20 min to obtain a modified starch solution; 5 parts by weight of emulsified paraffin and 25 parts by weight of filler (the filler comprises 15 parts by weight of quartz powder and 10 parts by weight of titanium dioxide) were added to the modified starch solution, and the particle size of the filler was 0.01 μm. The mixture was placed in a 40 KHz ultrasonic oscillation for 5 min, and the mixture was evenly dispersed to obtain a mixed solution B.
[0042] When using, first mix the mixed liquid A and the pulp evenly, mechanically stir for 10 minutes, then add the mixed liquid B and continue to stir evenly, mechanically stir for 10 minutes, so that the mixed liquid A and the mixed liquid B can be used as the fluorine-free oil-proof agent for pulp food containers and tableware. The addition ratio of the fluorine-free oil-proof agent is 6.25%. See Table 1.
[0043] Embodiment 2:
[0044] 4 parts by weight of polyacrylamide and 3 parts by weight of 2-ethylhexyl acrylate were added into 22 parts by weight of deionized water, and the mixture was stirred at a low speed of 65 rpm for 25 minutes to obtain a mixed solution A.
[0045] 3 parts by weight of modified starch were added to 28 parts by weight of deionized water, and the mixture was stirred evenly at a low speed of 65 rpm at a temperature of 75° C. for 25 min to obtain a modified starch solution; 8 parts by weight of emulsified paraffin and 30 parts by weight of filler (the filler comprises 18 parts by weight of quartz powder and 12 parts by weight of titanium dioxide) were added to the modified starch solution, and the particle size of the filler was 5 μm. The mixture was placed in a 40 KHz ultrasonic oscillation for 8 min, and the mixture was evenly dispersed to obtain a mixed solution B.
[0046] When using, first mix the mixed liquid A and the pulp evenly, and stir mechanically for 15 minutes, then add the mixed liquid B and continue to stir evenly, and stir mechanically for 15 minutes, so that the mixed liquid A and the mixed liquid B can be used as the fluorine-free oil-proof agent for pulp food containers and tableware. The addition ratio of the fluorine-free oil-proof agent is 6.25%. See Table 1.
[0047] Embodiment 3:
[0048] 5 parts by weight of polyacrylamide and 4 parts by weight of 2-ethylhexyl acrylate were added into 25 parts by weight of deionized water, and the mixture was stirred at a low speed of 70 rpm for 30 minutes to obtain a mixed solution A after being uniformly mixed.
[0049] 4 parts by weight of modified starch were added to 30 parts by weight of deionized water, and the mixture was stirred at a low speed of 70 rpm at a temperature of 80° C. for 30 min to obtain a modified starch solution; 10 parts by weight of emulsified paraffin and 35 parts by weight of filler (the filler includes 20 parts by weight of quartz powder and 15 parts by weight of titanium dioxide) were added to the modified starch solution, and the particle size of the filler was 10 μm. The mixture was placed in a 40 KHz ultrasonic oscillation for 10 min, and the mixture was evenly dispersed to obtain a mixed solution B.
[0050] When using, first mix the mixed liquid A and the pulp evenly, and stir mechanically for 25 minutes, then add the mixed liquid B and continue to stir evenly, and stir mechanically for 25 minutes, so that the mixed liquid A and the mixed liquid B can be used as the fluorine-free oil-proof agent for pulp food containers and tableware. The addition ratio of the fluorine-free oil-proof agent is 6.25%. See Table 1.
[0051] Embodiment 4:
[0052] In this Example 4, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the adhesive includes 2 parts by weight of polyacrylamide and 2 parts by weight of hydroxypropyl methylcellulose. See Table 1.
[0053] Embodiment 5:
[0054] In this Example 5, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the adhesive includes 2 parts by weight of polyacrylamide and 2 parts by weight of chitosan. See Table 1.
[0055] Embodiment 6:
[0056] In this Example 6, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the binder is 4 parts by weight of hydroxypropyl methylcellulose (or chitosan, or low-substituted hydroxypropyl cellulose, or polyvinyl pyrrolidone). See Table 1.
[0057] Embodiment 7:
[0058] In Example 7, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the adhesive includes 2 parts by weight of polyacrylamide, 1 part by weight of hydroxypropyl methylcellulose and 1 part by weight of chitosan. See Table 1.
[0059] Embodiment 8:
[0060] In Example 8, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the adhesive includes 2 parts by weight of polyvinyl pyrrolidone and 2 parts by weight of chitosan. See Table 1.
[0061] Embodiment 9:
[0062] In Example 9, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the binder includes 2 parts by weight of polyvinyl pyrrolidone and 2 parts by weight of low-substituted hydroxypropyl cellulose. See Table 1.
[0063] Embodiment 10:
[0064] In Example 10, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the filler is 30 parts by weight of quartz powder (or titanium dioxide, or montmorillonite, or silicon dioxide, or calcium carbonate). See Table 1.
[0065] Embodiment 11:
[0066] In Example 11, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the filler includes 18 parts by weight of quartz powder and 12 parts by weight of montmorillonite. See Table 1.
[0067] Embodiment 12:
[0068] In Example 12, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the filler includes 18 parts by weight of quartz powder and 12 parts by weight of silicon dioxide. See Table 1.
[0069] Embodiment 13:
[0070] In Example 13, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the filler includes 18 parts by weight of montmorillonite and 12 parts by weight of titanium dioxide. See Table 1.
[0071] Embodiment 14:
[0072] In Example 14, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the filler includes 18 parts by weight of montmorillonite and 12 parts by weight of silicon dioxide. See Table 1.
[0073] Embodiment 15:
[0074] In Example 15, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the filler includes 15 parts by weight of quartz powder, 10 parts by weight of titanium dioxide and 5 parts by weight of montmorillonite. See Table 1.
[0075] Embodiment 16:
[0076] In Example 16, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the filler includes 10 parts by weight of quartz powder, 10 parts by weight of titanium dioxide, 5 parts by weight of montmorillonite and 5 parts by weight of silicon dioxide. See Table 1.
[0077] Embodiment 17:
[0078] In Example 17, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the filler includes 18 parts by weight of quartz powder and 12 parts by weight of calcium carbonate. See Table 1.
[0079] Embodiment 18:
[0080] In Example 18, a fluorine-free oil-proof agent for pulp food containers and tableware is obtained by referring to the production process of Example 2. The difference from Example 2 is that the filler includes 18 parts by weight of montmorillonite and 12 parts by weight of calcium carbonate. See Table 1.
[0081] Comparative Example 1;
[0082] Comparative Example 1 A fluorine-free oil-proof agent for pulp food containers and tableware was obtained by referring to the production process of Example 2, and the difference from Example 2 is that 2-ethylhexyl acrylate is replaced by butyl acrylate. See Table 1.
[0083] Comparative Example 2;
[0084] Comparative Example 2 A fluorine-free oil-proof agent for pulp food containers and tableware was obtained by referring to the production process of Example 2, the difference from Example 2 being that polyacrylamide was replaced by sodium carboxymethyl cellulose (or sodium alginate, or polyvinyl alcohol). See Table 1.
[0085] Comparative Example 3;
[0086] Comparative Example 3 A fluorine-free oil-proof agent for pulp food containers and tableware was obtained by referring to the production process of Example 2, and the difference from Example 2 is that quartz powder and titanium dioxide are replaced by talcum powder (or bentonite, or diatomaceous earth). See Table 1.
[0087] Table 1
[0088]
[0089]
[0090]
[0091]
[0092] Example 19: Performance Testing Experiment
[0093] The pulp food container and tableware samples to which the fluorine-free oil-proofing agents prepared in Examples 1-18 and Comparative Examples 1-3 were added were placed on a platform plate or a flat plate of filter paper, and hot water and cooking oil at relative temperature were added to one third of the capacity of the pulp tableware. After being kept still at a constant temperature for 36 hours, the pulp tableware was observed for oil stains. The test results are shown in Table 2.
[0094] Table 2 Waterproof and oilproof test results
[0095]
[0096]
[0097] As shown in Table 2, in Examples 1 to 3, 2-ethylhexyl acrylate is used to provide a low surface energy environment, quartz powder and titanium dioxide are used to fill the gaps between fibers to improve the high temperature resistance, emulsified paraffin can cover and seal the hydrophilic groups on the fiber surface, and the modified starch forms a denser film under the synergistic effect of polyacrylamide. There is no penetration after the experiment is kept constant at 95°C hot water and 95°C cooking oil for 36 hours, which effectively improves the waterproof and oil-proof effect of the tableware. In addition, there is no penetration after the experiment is kept constant at 100°C hot water and 150°C cooking oil for 24 hours, and the waterproof and oil-proof effect is also relatively good.
[0098] As shown in Table 2, in Examples 4 to 9, quartz powder and titanium dioxide were used to fill the gaps between the fibers to improve the high temperature resistance, and the adhesive was replaced by other combinations from polyacrylamide. In the experiment, there was no penetration after 95°C hot water and 95°C cooking oil were kept at a constant temperature for 36 hours. In addition, there was still no penetration after 100°C hot water and 150°C cooking oil were kept at a constant temperature for 24 hours.
[0099] As shown in Table 2, in Examples 8 to 18, the same adhesive polyacrylamide was used, and the fillers were other combinations except for the combination of quartz powder and titanium dioxide. There was no penetration after the experiment was kept constant at 95°C hot water and 95°C cooking oil for 36 hours. In addition, there was no penetration after the experiment was kept constant at 100°C hot water and 150°C cooking oil for 24 hours.
[0100] As can be seen from Table 2, in Comparative Example 1 and Comparative Example 2, although quartz powder and titanium dioxide are used to fill the gaps between the fibers, whether butyl acrylate is used to provide a low surface energy environment or sodium carboxymethyl cellulose (or sodium alginate, or polyvinyl alcohol) is used as an adhesive, the effects of whether the experiment is to hold 95°C hot water and 95°C edible oil at a constant temperature for 36 hours, and whether the experiment is to hold 100°C hot water and 150°C edible oil at a constant temperature for 24 hours, are not as good as those of Examples 1 to 3 of the present invention; in Comparative Example 3, although 2-ethylhexyl acrylate is used to provide a low surface energy environment and polyacrylamide is used as an adhesive, talcum powder (or bentonite, or diatomaceous earth) is used as a filler, and whether the experiment is to hold 95°C hot water and 95°C edible oil at a constant temperature for 36 hours, and whether the experiment is to hold 100°C hot water and 150°C edible oil at a constant temperature for 24 hours, are not as good as those of Examples 1 to 3 of the present invention.
[0101] It can be seen that the fluorine-free oil-proofing agent prepared by the present invention provides a low surface energy environment through 2-ethylhexyl acrylate, and the filler is selected from one or more of calcium carbonate, quartz powder, titanium dioxide, montmorillonite, and silicon dioxide to fill the gaps between the fibers. The emulsified paraffin can cover and seal the hydrophilic groups on the fiber surface. The modified starch forms a denser film under the synergistic effect of the adhesive. The adhesive is selected from one or more of hydroxypropyl methylcellulose, low-substituted hydroxypropyl cellulose, polyvinyl pyrrolidone, polyacrylamide, and chitosan, which effectively improves the oil-proof effect of tableware. The pulp food container and dining utensils added with the fluorine-free oil-proofing agent prepared by the present invention have no penetration after being kept at a constant temperature for 36 hours at 95°C hot water and 95°C edible oil, and can achieve a good waterproof and oil-proof effect. In addition, there is no penetration after being kept at a constant temperature for 24 hours when 100°C hot water and 150°C edible oil are placed, and the waterproof and oil-proof effect is also relatively good.
[0102] Example 20: Acute oral toxicity test
[0103] Based on GB15193.3-2014 national food safety standard.
[0104] Under the experimental conditions, the fluorine-free oil repellent obtained in Examples 1-18 as the test sample has an acute oral LD50 of >5000 mg / Kg for ICR mice. According to the acute toxicity classification, the fluorine-free oil repellent obtained in the present invention belongs to the practically non-toxic grade.
[0105] 1. Materials and Methods
[0106] 1.1. Test sample processing
[0107] Weigh 10.0900g of sample and place it in a beaker. Take a small amount of pure water to mix the sample and transfer it to a 20mL volumetric flask. Rinse the beaker with a small amount of pure water several times and transfer the sample to the volumetric flask. Add pure water to make up to the scale line. Shake well and transfer to a sample tube and mark for use. The sample should be prepared and used immediately.
[0108] Gavage volume: 2.0mL / 100g·BW
[0109] 1.2.Solvent: Millipore pure water;
[0110] 1.3 Experimental animals
[0111] Species: Mouse;
[0112] Strain: ICR;
[0113] Level: SPF level;
[0114] Number of animals: 20;
[0115] Animal gender: half male and half female, female animals are not pregnant and have never given birth;
[0116] Age: 6 weeks old;
[0117] Weight: 18.7g~21.9g, weight of the same sex should not exceed ±20% of the mean;
[0118] 1.4. Test methods
[0119] The animals were adapted to the experimental animal room environment for 3 days before the test, and fasted overnight before exposure. After the test began, a maximum test was used, with an oral dose of 5069.3 mg / kg. After exposure, the animals continued to fast for 3 hours, observed poisoning symptoms or behavioral changes every day, and weighed once a week. The poisoning process and the poisoning and death of animals during the observation period were observed and recorded. The observation period was 14 days. After the observation period, the surviving animals were killed and grossly dissected.
[0120] 2. Test results
[0121] The experimental animals showed no symptoms of poisoning or death within 14 days of exposure; the weight of male and female animals was normal. At the end of the experimental observation, no abnormal changes were found in the gross anatomical examination of the test animals. LD50>5000mg / kg. See Table 3.
[0122] 3. Experimental conclusion
[0123] Under the experimental conditions, the fluorine-free oil repellent obtained in Examples 1-18 as the test sample has an acute oral LD50 of >5000 mg / kg for ICR mice. According to the acute toxicity classification, the fluorine-free oil repellent obtained in the present invention belongs to the practically non-toxic grade.
[0124] Table 3 Acute oral toxicity test results
[0125]
[0126] It should be noted that the above invention content and specific implementation methods are intended to demonstrate the practical application of the technical solution provided by the present invention and should not be interpreted as limiting the scope of protection of the present invention. Those skilled in the art can make various modifications, equivalent substitutions or improvements within the spirit and principles of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A production process for a fluorine-free oil-proofing agent for pulp food containers and tableware, characterized in that: The production process comprises the following steps: (1) adding 4 parts by weight of polyacrylamide and 3 parts by weight of 2-ethylhexyl acrylate to 22 parts by weight of deionized water, stirring at a low speed to obtain a mixed solution A; the stirring time in step (1) and step (2) is 20 to 30 minutes, and the stirring speed is 60 to 70 rpm; (2) adding 3 parts by weight of modified starch to 28 parts by weight of deionized water, stirring at a low speed at a temperature of 75° C. to obtain a modified starch solution; the modified starch is cationic starch or anionic starch; (3) adding 8 parts by weight of emulsified paraffin, 18 parts by weight of quartz powder and 12 parts by weight of titanium dioxide to the modified starch solution obtained in step (2), performing ultrasonic vibration, and obtaining a mixed solution B after uniform dispersion; the particle size of the quartz powder and titanium dioxide is 5 μm; placing the solution in an ultrasonic cleaner at an ultrasonic frequency of 40 KHz and performing ultrasonic vibration for 5 to 10 minutes in step (3); (4) When using, first mix the mixed liquid A and the pulp evenly, then add the mixed liquid B and continue to mix evenly, so that the mixed liquid A and the mixed liquid B can be used as the fluorine-free oil repellent for pulp food containers and tableware.
2. The production process according to claim 1, characterized in that: In step (4), the solution A and the pulp are mechanically stirred for 5 to 25 minutes, and then the solution B is added and mechanically stirred for another 5 to 25 minutes.
Citation Information
Patent Citations
Fluoride-free type waterproof agent and preparation method thereof
CN108893985A
Starch-based biological fluoride-free oil-proofing agent, emulsifying system for preparing oil-proofing agent and production process of oil-proofing agent
CN111851136A
Fluorine-free waterproof and oil-proof agent used in paper pulp molding pulp and use method of fluoride-free waterproof and oil-proof agent
CN114164704A